Description of two new species of Diastrophus Hartig, 1840 from Taiwan, Diastrophus renai and D. wushei (Hymenoptera: Cynipidae: Diastrophini) - Davis, Charles K.; Nastasi, Louis F.; Deans, Andrew R. (Zootaxa, 2024)
We describe Diastrophus wushei Davis & Nastasi sp. nov. and D. renai Davis & Nastasi sp. nov., two gall wasp species collected on Wushe Mountain, Taiwan by the late Henry Townes. These species represent the first Diastrophini and potentially the first non-Fagaceae associated species of gall wasp described from Taiwan. We speculate on potential hosts plants for further study and possible avenues to elucidate their biology.